STEREOTIP DAN PRASANGKA KOMUNIKASI ANTAR PEMERAN FILM KOS-KOSAN DENGAN PESPEKTIF WACANA KRITIS MILLS - Maria Borges, Serilio Verdial; Marta, Rustono Farady; Panggabean, Hana Rochani Gustasari; Briandana, Rizki; Chinmi, Maichel (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
Visual media is a very popular communication media in society, with short films being particularly accessible and easily interpreted by viewers. This research aims to analyse a short film titled "Kos - Kosan", which address the issue of prejudice and stereotypes related to religious conflict, focusing on the subject-object position, author-reader positions depicted in the scenes shown. Using Sara Mills' Critical Discourse Analysis and a descriptive qualitative analysis method, this study seeks to describe the impact on women and explore the perspective and actions taken by viewers of the short film plot towards the object, women. This study found that the conflict that occurs is primarily due to misunderstandings in communication, where the subject directs the object toward an understanding that negative connotation. Similarly, viewers tend to perceive women in terms of immorality and promiscuity rather than discrimination and intolerance. One of the factors causing misunderstandings in communication between the actors of this short film is nonverbal communication, including facial expressions and body language, which often lead to misinterpretation.